“O mundo não acaba no Malecón” : exílio, intelectuais e dissidência política nas revistas Encuentro de la Cultura Cubana e Revista Hispano-Cubana (1996-2002) - Thiago Henrique Oliveira Prates (2015)
This M.A. thesis investigates how Cuban exiled intellectuals criticized Castro’s regime through the pages of cultural magazines Encuentro de la Cultura Cubana and Revista Hispano-Cubana, both published in Madrid during the 1990’s. We examine how these publications and spaces of intellectual sociability formed an opposition to the Cuban socialist government, comparing how both magazines used the subject of exile to attack the regime. We also discuss the Cuban intellectual, source of legitimacy of the exiled's dissident narrative, and the political ideas of each magazine, observing how the experience of exile always influenced the portraits of Cuba, and the opposition discourses. Through this thesis, we have shown the transnational connections between the island and the exile, the links between the magazines and Spanish politics, their interpretations of the past, their political stances and propositions to the island. To do so, we set the timeframe between 1996, when Encuentro de la Cultura Cubana was first published, and 2002, the year of passing of that magazine’s then director, Jesús Díaz, and Revista Hispano-Cubana changed its directive board.